2011
DOI: 10.1115/1.4003417
|View full text |Cite
|
Sign up to set email alerts
|

Splitting Water and Carbon Dioxide via the Heterogeneous Oxidation of Zinc Vapor: Thermodynamic Considerations

Abstract: The heterogeneous oxidation of zinc vapor is proposed as a promising reaction path for the exothermic step in the two-step Zn/ZnO solar thermochemical water and carbon dio.xide splitting cycles. This approach circumvents mass transfer limitations encountered in the oxidation of solid or liquid zinc, promising rapid hydrogen and carbon monoxide production rates concurrent with a complete conversion of zinc to zinc oxide. In this paper, a parametric thermodynamic analysis is presented to quantify the benefit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The enhanced SSA of the 3-DOM ceria and its interconnected pore system, which facilitated the transport of reacting species to and from oxidation sites, was given as the cause of this increase in the kinetics of CO 2 splitting (Venstrom et al, 2012). This was the first work to clearly demonstrate the benefits of a regular 3-DOM network structure on CO production rates, albeit with quite small cells of only ~0.4 μm (Venstrom, 2012).…”
Section: Three-dimensionally Ordered Macroporous (3-dom) Ceriamentioning
confidence: 93%
See 1 more Smart Citation
“…The enhanced SSA of the 3-DOM ceria and its interconnected pore system, which facilitated the transport of reacting species to and from oxidation sites, was given as the cause of this increase in the kinetics of CO 2 splitting (Venstrom et al, 2012). This was the first work to clearly demonstrate the benefits of a regular 3-DOM network structure on CO production rates, albeit with quite small cells of only ~0.4 μm (Venstrom, 2012).…”
Section: Three-dimensionally Ordered Macroporous (3-dom) Ceriamentioning
confidence: 93%
“…For an isothermal cycle at 800°C, CO production rates as a function of (B) time and (C) reaction extent for CO 2 splitting for commercial ceria, DS ceria and 3-DOM pure ceria. Adapted from Venstrom (2012), ©Luke J. Venstrom.…”
Section: Three-dimensionally Ordered Macroporous (3-dom) Ceriamentioning
confidence: 99%
“…Thermodynamic calculations have shown that it increases with an increase in the yield of fuel (H 2 and/or CO), thus the extent of both reactions 1 and 2 . 5 However, it has also been shown that achieving a high extent of reaction 1 requires ultrafast quenching of the product mixture to suppress the recombination of Zn-vapor and O 2 . 1 This task is generally performed by mixing substantial amounts of inert gas with the solar reactor product stream, 6 which adversely affects the cycle efficiency due to the additional energy required for purification and recycling of the inert gas quencher.…”
Section: Introductionmentioning
confidence: 99%
“…Solar thermochemical cycles on the production of CO by splitting CO 2 with metal/metal-oxide redox pairs have been widely investigated, since the character of coping with the energy crisis and increasing carbon emissions. Such redox pairs include volatile metal oxides (e.g., Zn/ZnO and SnO/SnO 2 , ) and nonvolatile metal oxides (e.g., FeO/Fe 3 O 4 , ,, ferrite cycles, , CeO 2 /Ce 2 O 3 , , and doped ceria cycles ,, ). Venstrom et al stated that the maximum theoretical thermal efficiency for the dissociation of CO 2 with Zn vapor could reach 31% without heat recovery. Thus, the two-step thermochemical cycle for the splitting of CO 2 based on Zn/ZnO emerges as one of the promising cycles.…”
Section: Introductionmentioning
confidence: 99%